SARS-CoV-2 in pediatrics. History of a pandemic from China to Colombia - Urbano Arcos, Julieth Fernanda; Ruiz Ponce de Leon, Isabel; Oliveros, Oskar Andrey; Mejia Rivera, Luis Fernando; Rojas Hernandez, Juan Pablo (Interdisciplinary Journal of Epidemiology and Public Health, 2020)
Introduction: Coronavirus until 1930 were part of the viruses that only disturbed the animal niche. Severe acute respiratory syndrome due to coronavirus 2 (SARS-CoV-2) a type of coronavirus that causes coronavirus disease (COVID-19); In the last year it has become a concern for international public health due to the triggered pandemic, due to its high transmissibility and high mortality that it has caused. Objective: describe SARS-COV-2 infection in pediatrics with special emphasis on virological, epidemiological aspects, transmission mechanism, clinical manifestations, and expectations of treatment in pediatric age. Methods: A review of articles in Spanish and English was made, using valid terms, on the PubMed, ScienceDirect and Medline databases related to the disease. Articles with a publication period of no more than 5 years were considered. Results: The epidemiology, pathophysiology, clinical manifestations, complications, isolation and possibilities of treatment of SARS-CoV-2 in pediatric age are described. Conclusions: SARS-CoV-2 is highly contagious, the pediatric population has mostly mild clinical manifestations. The importance of an appropriate approach in this population is to avoid spreading to other ages of greater morbidity and mortality and possible associated complications.